Oxalate-bridged heterometallic chains with monocationic dabco derivatives - Sakurai, Takahiro; Saiki, Ryo; Wei, Rong Jia; Newton, Graham; Shiga, Takuya; Oshio, Hiroki (Royal Society of Chemistry, 2016)
A series of bimetallic oxalate-bridged one-dimensional chains with monocationic dabco derivatives, (R-dabco[M(solv)2][Cr(ox)3]·n(solv)) (dabco = 1,4-diazabicyclo[2.2.2]octane, H2ox = oxalate; R = H, M = Co (1); R = H, M = Zn (2); R = Bu, M = Co (3); R = Bu, M = Zn (4)) were synthesized. All compounds have one-dimensional zig-zag chain structures with R-dabco cations located between chains. Cryomagnetic studies reveal that 1 and 3 showed intrachain ferromagnetic interactions between Co(II) and Cr(III) ions and metamagnetic behaviour due to interchain antiferromagnetic interactions. Permittivity measurements on compound 4 indicate specific paraelectronic relaxation behaviour originating from the rotational motion of the dabco alkyl substituent.